2011
DOI: 10.1111/j.1540-8167.2011.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients Treated with Catheter Ablation for Atrial Fibrillation Have Long‐Term Rates of Death, Stroke, and Dementia Similar to Patients Without Atrial Fibrillation

Abstract: AF ablation patients have a significantly lower risk of death, stroke, and dementia in comparison to AF patients without ablation. AF ablation may eliminate the increased risk of death and stroke associated with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
228
4
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(250 citation statements)
references
References 42 publications
(82 reference statements)
8
228
4
10
Order By: Relevance
“…239,1112,1113,1114 In a very large, prospectively collected registry (the Intermountain Healthcare Database in Utah), investigators reported a significantly lower rate of stroke in 4212 ablated patients (follow-up 3.1 ± 2.4 years), compared with those who did not undergo ablation. 239 Moreover, ablated patients had comparable stroke rates when compared with age- and sex-matched patients who did not have a history of AF. Both observations were independent of baseline stroke risk score.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…239,1112,1113,1114 In a very large, prospectively collected registry (the Intermountain Healthcare Database in Utah), investigators reported a significantly lower rate of stroke in 4212 ablated patients (follow-up 3.1 ± 2.4 years), compared with those who did not undergo ablation. 239 Moreover, ablated patients had comparable stroke rates when compared with age- and sex-matched patients who did not have a history of AF. Both observations were independent of baseline stroke risk score.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…Bunch age/gender matched controls without AF. 36 The results showed that AF ablation patients have a significantly lower risk of death, stroke …”
Section: Could Catheter Ablation Of Atrial Fibrillation Reduce Long-tmentioning
confidence: 89%
“…[1] Catheter ablation, which is centered on electrical isolation of triggering foci within the pulmonary veins (PV) through circumferential lesions around PV ostia, has been shown to result in sustained improvements in quality of life, decreased hospitalizations and, potentially, improved survival. [4-6]…”
Section: Introductionmentioning
confidence: 99%